Oceania’s ‘crimmigration creep’: Are deportation and reintegration norms being diffused? - McNeill, Henrietta (Journal of criminology, 2021)
The trend of deportation of convicted non-citizens to the Pacific has grown over the last decade, due to increasingly harsh deportation punitive measures placed on non-citizens, known as crimmigration. When further parole-like policies and legislation are placed upon the returnee once they have completed their sentence and have been returned to their country of origin, it is known as ?crimmigration creep?. ?Crimmigration creep? has been seen in the New Zealand Returning Offenders (Management and Information) Act (2015), and appears to be proposed in the similar Samoan Returning Offenders Bill (2019). This article tests the diffusion of ?crimmigration creep? to understand how international relations norm diffusion theory can be applied to border criminology concepts. This is done within a norm circulation model, and by testing the normative strength of ?crimmigration creep? in Samoa.